2016
DOI: 10.5994/jei.13.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi pelepasan Trichogramma spp. untuk pengendalian penggerek pucuk dan batang tebu

Abstract: ABSTRAKEvaluasi keberhasilan dan efektivitas pengendalian hayati menggunakan Trichogramma spp. untuk mengendalikan penggerek pucuk dan batang tebu belum pernah dilakukan secara intensif. Penelitian ini bertujuan untuk mengevaluasi teknik pengendalian kompleks penggerek tebu dengan pelepasan Trichogramma spp. Evaluasi dilakukan dengan pendekatan pengujian keragaan parasitoid telur melalui penghitungan laju reproduksi dan kemampuan parasitisasi parasitoid pada telur Corcyra cephalonica (Stainton), telur inang ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…After release reported that Scirpophaga spp. was not parasitized by Trichogramma spp [24][25][26]. Unlike Scirpophaga spp., Chilo spp.…”
Section: Estate Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…After release reported that Scirpophaga spp. was not parasitized by Trichogramma spp [24][25][26]. Unlike Scirpophaga spp., Chilo spp.…”
Section: Estate Cropsmentioning
confidence: 99%
“…reported could be parasitized by Trichogramma spp. Two evaluations observed the level of parasitization after release compared to several plantations without release treatment [25][26]. The evaluation reported that the highest level of parasitization by Trichogramma spp.…”
Section: Estate Cropsmentioning
confidence: 99%
“…Previous studies have reported various parasitoid species associated with S. excerptalis eggs on sugarcane, including Trichogramma chilonis, Telenomus dignoides, Tetrastichus schoenobii, Telenomus beneficiens, and Trissolcus spp. [22,23,24,25,26]. Telenomus spp.…”
Section: Telenomus Spmentioning
confidence: 99%
“…In East Java, Telenomus sp. dominated the parasitism of S. excerptalis eggs, reaching 100% parasitism rates [26].…”
Section: Telenomus Spmentioning
confidence: 99%